2019
DOI: 10.1093/eurheartj/ehz564
|View full text |Cite
|
Sign up to set email alerts
|

Mortality reduction with physical activity in patients with and without cardiovascular disease

Abstract: Aims Physical activity has been shown to reduce mortality in a dose-response fashion. Current guidelines recommend 500–1000 metabolic equivalent task (MET)-min per week of regular physical activity. This study aimed to compare the impact of leisure-time physical activity on mortality in primary versus secondary cardiovascular prevention. Methods and results This study included a total of 131 558 and 310 240 subjects with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
141
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(181 citation statements)
references
References 46 publications
10
141
1
8
Order By: Relevance
“…Although there is substantial epidemiological evidence that higher levels of MVPA are associated with better medical outcome and quality of life in patients with CHD, 24 there is considerably less evidence about interventions that can help patients maintain activity levels following completion of CR 7 . In the present trial, a 50-week, home and community-based, remotely-delivered EFI was shown to beneficially impact MVPA in women who adhered to the intervention sessions (almost 3/4s of the J o u r n a l P r e -p r o o f women) compared to UC; the intervention was ineffective in men, who were already quite active.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is substantial epidemiological evidence that higher levels of MVPA are associated with better medical outcome and quality of life in patients with CHD, 24 there is considerably less evidence about interventions that can help patients maintain activity levels following completion of CR 7 . In the present trial, a 50-week, home and community-based, remotely-delivered EFI was shown to beneficially impact MVPA in women who adhered to the intervention sessions (almost 3/4s of the J o u r n a l P r e -p r o o f women) compared to UC; the intervention was ineffective in men, who were already quite active.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Moreover, physical activity improves prognosis in a dose-response fashion, and individuals at higher risk may benefit from physical activity to a greater extent than those at a lower risk. 18 Hearing and vision problems may be treated with appropriate glasses and hearing devicesthis is critical because such sensory deficits predispose to frailty development. [19][20][21] Feeling down, nervousness and anxiety, as well as missing other people were the most dominant psychological and social problems among this study subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an earlier study found that there are weaker relative educational disparities in mortality among adults with vs those without diabetes [ 10 ]. The benefit from physical activity in individuals with CVD was shown to be greater than that in healthy individuals without CVD [ 11 ]. Mounting epidemiological evidence suggests that sleep duration is related to increased risks of CVD events and higher mortality risk in the general population [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%